The Order of the City Three Fortresses Adjacent to the Sultanate of Buton in the Local Culture-Based Hilly Landscape of Baubau City of Southeast Sulawesi - Mansyur, Abdul; Manarfa, La Ode Muhammad Rauda Agus Udaya (GMPI Conference Series, 2023)
The Sultanate of Buton whose Sultan is called khalifatul khamis was formed in 1332 and became one of the past Islamic civilizations. Historically, the land of the royal city center was discovered, pioneered and built by four groups of immigrants from Johor. In addition to its interactions with local neighboring kingdoms in the archipelago and several European countries, the city of the Sultanate of Buton was once occupied by the kings of Mecca, Arabs, and Turkish rulers who also controlled the city. The results of the study found that several relics can be found in this area, including three city forts built on a hilly landscape, namely (1) Fort Kotana Wolio, (2) Fort Kotana Sorawolio, and (3) Fort Kotana Baadia. In position, these three forts have a unique arrangement and character that forms a triangular pattern. The triangular pattern places the Kotana Wolio Fort - Buton Palace like the Imam and the Kotana Baadia Fort and the Kotana Sorawolio Fort as the Ma'mum, all of which face west as if they were praying facing the Kaaba. Thus, during the sultanate, the function of the city fort was for defense and interconnectivity between forts that became strategic and effective. Especially in the historical context of the old city, it will be difficult to understand because of its complexity. In this paper, with reference to the historical aspects and artifacts of the existing forts, the discussion is to identify the order (position and layout, distance between forts, and urban land area), orientation patterns, public infrastructure, and runways. philosophy. Data collection methods used include field surveys, tracing of original manuscripts, and interviews with traditional leaders. For aerial photos, satellite images downloaded from Google earth are used, and other supporting materials from the results of previous studies are also used. Next, the collected data were analyzed and synthesized. In fact, every city fort is a residential area and Wolio City is the center and area of the first fort built; Thus, this paper is expected to contribute to sustainable urban planning or become a mirror for the formation of new cities.